Re-imagining Jakarta after capital city relocation using nature-based solutions: a journal article review - Sri Hayyu Alynda Heryati; Raldi Hendro T. Koestoer (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2022)
Relocation of the capital city from Jakarta to Nusantara does not necessarily reduce the population pressure and does not solve Jakarta's environmental problems. One of the newest concepts that mainstreaming urban resilience in order to adapt to the climate change impact is nature-based solutions. For this reason, it is necessary to look for the potential for this concept to be applied in Jakarta, which aims to contribute to a sustainable future city design for Jakarta. A qualitative descriptive study was conducted through a literature review by comparing case studies in various cities in the world to obtain information on the latest developments in the concept of nature-based solutions. Various nature-based solutions that have been successfully implemented by cities in the world can be adapted for implementation in Jakarta by taking into account their feasibility and suitability to the characteristics of Jakarta. The regeneration of Jakarta as a resilient and sustainable city can be done by prioritizing nature-based solutions, such as renaturalization and rewilding. Renaturalization is not only focused on park development, but on rainwater management and restoration of watershed quality with a multifunctional utilization design. In addition, well-managed rewilding can become an option to increase biodiversity. Various nature-based solutions that have been successfully implemented by cities in the world can be adapted for implementation in Jakarta by taking into account their feasibility and suitability to the characteristics of Jakarta. The focus of green city development which is only on the development of green open spaces has resulted in the failure to provide solutions to environmental issues and urban sustainability. Deeper citizen engagement is required for the implementation of inclusive nature-based solutions. With the increasing environmental challenges faced by Jakarta, it is necessary to transform the city into a more resilient and sustainable city with a holistic approach by adopting the concept of a circular city for the management of limited resources.